Traditional and industrial approaches to oil palm cultivation alter the biodiversity of ground-dwelling arthropods in Liberia (West Africa) - Timperley, Jonathan H.; Pett, Brogan L.; Geninyan, Bility; Saputra, Ari; Vincent, Abraham; Weah, Romeo; Freeman, Benedictus; Guahn, Marshall; Hadfield, Peter M.; Jah, Morris T.; Jones, Tiecanna; Widodo, Rudy H.; et al. (Elsevier, 2025)
Oil palm cultivation is vital to global food security and economically important to farmers. However, the rapid expansion of oil palm plantations has caused large-scale deforestation in the tropics and, consequently, biodiversity loss and changes in ecosystem functioning. Oil palm is primarily cultivated in Southeast Asia, where the ecological impacts of production have been studied extensively. It is also grown in West Africa, using traditional and industrial methods of cultivation. However, in comparison to Southeast Asia, relatively little research on the impacts of oil palm cultivation in West Africa has occurred. Working in the framework of the Sustainable Oil Palm in West Africa (SOPWA) Project (Sinoe County, Liberia), we investigated differences in the biodiversity of ground-dwelling arthropods across rainforest (the regional natural habitat) and oil palm systems cultivated under traditional (called “country palm”) and industrial management. We sampled arthropods with pitfall traps (160 retrieved) across 54 monitoring plots in rainforest, country palm, and industrial oil palm. We found no differences in total arthropod abundance across systems, but we did find changes in arthropod order-level community composition, driven by differences in the relative abundance of Araneae, Collembola, Dermaptera, and Diptera. We conducted focused morphospecies-level analyses on spiders, owing to their key roles as predators within tropical agricultural systems, and to determine if our order-level findings held true at increased taxonomic resolution. Our spider analyses indicated that country palm supported the greatest number of spider individuals and species, and that all systems supported distinct spider assemblages. Our findings have implications for both arthropod conservation and oil palm productivity, owing to the important ecosystem functions (e.g., pest control) that many arthropods provide. Future research should investigate whether changes in on-farm management practices influence arthropod communities - and the ecosystem functions they support - in West Africa.
Keywords: land use changes; tropical agriculture; Elaeis guineensis; invertebrate; insects; spiders